2018 IFIP/IEEE International Conference on Very Large Scale Integration (VLSI-SoC) 2018
DOI: 10.1109/vlsi-soc.2018.8644829
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Bioimpedance Spectroscopy Architecture for a Wide Frequency Exploration of Tissue Electrical Properties

Abstract: Bioimpedance spectroscopy (BIS) is a technique increasingly used for measuring the electrical properties of biological tissues. Choosing an integrated system architecture for bioimpedance spectroscopy is very dependent on the application and ruled by several constraints such as precision, bandwidth and measurement time. This paper presents a hybrid architecture providing fast measurement time while maximizing precision. This new architecture has been defined for a wide exploration of electrical properties of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The electrical characteristics of organisms will change with different organs and tissues. Generally, the impedance characteristics of different tissues are quite different (Lamlih et al, 2018). Table 1 is electrical conductivity of some common tissues and organs.…”
Section: Electrical Impedance Characteristics Of Biological Tissues Biological Electrical Characteristics Of Electric Currentmentioning
confidence: 99%
“…The electrical characteristics of organisms will change with different organs and tissues. Generally, the impedance characteristics of different tissues are quite different (Lamlih et al, 2018). Table 1 is electrical conductivity of some common tissues and organs.…”
Section: Electrical Impedance Characteristics Of Biological Tissues Biological Electrical Characteristics Of Electric Currentmentioning
confidence: 99%
“…; and γ, >10 MHz, for content measurement of the biological species (intracellular fluid level), etc. [24,29,30]. Since pain is an electrical signal transmitted by dynamics of potassium channels signaling among intra-and extracellular fluid, it seems natural to choose the lowest frequency dispersion for exciting the skin with our device.…”
Section: Multisine Designmentioning
confidence: 99%
“…In addition, it has already been shown that mathematical formulation is an important tool in characterization of drug tissue trapping [18]. The rationale of using bioimpedance spectroscopy is that it allows a rigorous characterization of the biological tissue electrical properties influenced by nociception [19,20]. The in-house developed prototype and methodology have the advantage to follow a customizable input signal that excites the tissue over a range of frequencies.…”
Section: Introductionmentioning
confidence: 99%